2014
DOI: 10.1021/ja507175b
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Interplay of Backbone Rigidity and Electron Rich Side-Chains on Electron Transfer in Peptides: The Realization of Tunable Molecular Wires

Abstract: Electrochemical studies are reported on a series of peptides constrained into either a 310-helix (1–6) or β-strand (7–9) conformation, with variable numbers of electron rich alkene containing side chains. Peptides (1 and 2) and (7 and 8) are further constrained into these geometries with a suitable side chain tether introduced by ring closing metathesis (RCM). Peptides 1, 4 and 5, each containing a single alkene side chain reveal a direct link between backbone rigidity and electron transfer, in isolation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 44 publications
3
58
0
Order By: Relevance
“…17 Furthermore, 1 H NMR J NHCαH coupling constants consistent with a β-strand structure 18 were observed for these peptides. The conformations of 3 and 4 were confirmed as 3 10 -helical, based on observed CαH(i) to NH(i+1) and medium range CαH(i) to NH(i+2) ROESY correlations 5 ( Fig. S3 and S4).…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…17 Furthermore, 1 H NMR J NHCαH coupling constants consistent with a β-strand structure 18 were observed for these peptides. The conformations of 3 and 4 were confirmed as 3 10 -helical, based on observed CαH(i) to NH(i+1) and medium range CαH(i) to NH(i+2) ROESY correlations 5 ( Fig. S3 and S4).…”
Section: Resultsmentioning
confidence: 77%
“…These values are comparable to other carbon nanotube electrode studies. 5,6,24 The formal potentials (E o ) and apparent electron transfer rate constants (k et ) were estimated using Laviron's formalism ( Fig. 3b and 3d, Table 1).…”
Section: Electron Transfer In Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Studies with α-aminoisobutyric acid-rich hexapeptides, constrained into a 3 10 -helix and β-sheets, demonstrated that the presence of CC bonds influences backbone rigidity and promotes electron transfer across the peptide. 12,13 Solid-state electron transport measurements via different protein monolayers have shown that at room temperature (RT) ETp across bR is comparatively more efficient than across the globular proteins that we have measured so far, taking in account the differences in transport length across the protein. 6 In view of this, we examined whether Halorhodopsin (phR) as a homologue of bacteriorhodopsin (bR) might be even more efficient conductor, when immobilized with bacterioruberin oriented perpendicular to the electrodes ( Figure 1, right, device scheme).…”
mentioning
confidence: 99%